The assessment of energy demand in the new olympic windsurf board: Neilpryde RS:X® - Castagna, O.; Pardal, C. V.; Brisswalter, J. (European Journal of Applied Physiology, 2007)
The aim of this study was to evaluate the energy demands of sailing the new Neilpryde RS:X® Olympic windsurf board. Ten skilled male subjects performed an exhaustive incremental treadmill test to determine their maximal physiological parameters. Thereafter, four tests were performed in a randomised order using two wind conditions, light [2-4 ms-1 (4-8 knots)] and strong: [9-11 ms-1(16-22 knots)]. Oxygen consumption ( \ifmmode\expandafter\dot\else\expandafter\.\fi{V}{\text{O}}_{2} , ml min-1 kg-1), blood lactate concentration ([la]b, mmol l-1), and time spent pumping (% total time) were recorded during 10 min of up-wind leg and during 6 min of down-wind leg. The results indicate that sailing on RS:X is associated with a high level of energy demand using both aerobic and anaerobic pathways whatever the wind conditions. During the down-wind leg, \ifmmode\expandafter\dot\else\expandafter\.\fi{V}{\text{O}}_{2} (ml min-1 kg-1), [la]b (mmol l-1), and time spent pumping (% total time) values for the light and strong wind conditions were 56.5 ± 5.9 versus 55.5 ± 3.6; 10.2 ± 1.5 versus 9.6 ± 2.3, and 69 ± 5 versus 64 ± 2%, respectively. In contrast, during up-wind leg the same parameters for light and strong wind were 53.9 ± 4.5 versus 40.4 ± 7.2; 9.7 ± 2.8 versus 5.0 ± 2.7 and 66 ± 3 versus 37 ± 8%, respectively. During the up-wind leg with strong wind conditions, less time was spent pumping (p < 0.05), mean oxygen consumption values were close to 60% \ifmmode\expandafter\dot\else\expandafter\.\fi{V}{\text{O}}_{{2\max }} , and post-exercise blood lactate was less than 50% maximal lactate concentration. These results could be related to the time spent in pumping action, involving whole body activity. When sailing with the RS:X board, the physiological demand seems to be higher than with the previous official Olympic windsurf board [Mistral One Design® (MOD)]. This difference could be mainly attributed to the specific biomechanical constraints induced by each board characteristic.